Modified vendettas as a method of punishing corporations - Shipp, Shannon (Journal of business ethics, 1987)
Methods of punishing corporations have changed from self-regulation to economic sanctions by government as corporations have evolved from small groups of entrepreneurs to multinational entities. It is proposed that the next stage in the evolution of punishment methods is modified vendettas, or organized attempts by non-government groups to influence corporations through the application of economic and non-economic sanctions., This paper develops the concept of modified vendettas as a complement to government-initiated economic sanctions. The effectiveness of modified vendettas is analyzed through two case examples. As with any punishment method, however, the usefulness of a modified vendetta depends not only on its effectiveness but also on how well it meets society's needs to monitor and check corporate activity while preserving corporations' rights to operate. To resolve this issue, modified vendettas are assessed using a philosophical framework incorporating both retributive and utilitarian principles. It is found that modified vendettas extend society's ability to control corporate behavior while corporations have legal and public relations means to protect themselves from frivolous use of the technique., Did you ever expect a corporation to have a conscience, when it has no soul to be damned, and no body to be kicked?, (Baron Thurlow)